2018
DOI: 10.1108/wje-11-2017-0353
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic reduction using a novel multipulse AC-DC converter

Abstract: Purpose For direct torque controlled induction motor drives, an effective solution to eliminate harmonics is the use of multipulse alternating current (AC)-direct current (DC) converters. Many researchers have used different configurations based on 24- and 30-pulse rectifications for improved power quality. However, the total harmonic distortion (THD) of AC mains current with these topology is more than 4 per cent when operating at a light load. For mitigating the THD problems observed in the input currents, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, these topologies have high magnetic ratings and are therefore expensive. Increasing the number of pulses reduces the current THD but with the additional complexity and cost of MPRs [27][28][29][30][31][32][33]. On the other hand, the use of passive or active filters can also lead to current THD reduction [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…However, these topologies have high magnetic ratings and are therefore expensive. Increasing the number of pulses reduces the current THD but with the additional complexity and cost of MPRs [27][28][29][30][31][32][33]. On the other hand, the use of passive or active filters can also lead to current THD reduction [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Thus Drain to Source Resistance is ON for power switch is required. Again, input current of the proposed converter is proceeded; thus, weight on the info source is reduced (Abdollahi, 2018;YiyangLi and Sathiakumar, 2017;Babaei et al, 2017). The working standards and relentless state examinations are discussed in detail for both continuous conduction mode and discontinuous conduction mode.…”
Section: Introductionmentioning
confidence: 99%
“…As passive PFC is still widely used because of its simplicity, so in order to further explore the HB converter, a passive PFC technique is also implemented to improve the power quality of the converter. The other PFC methods such as active PFC methods could also applied to achieve better PF, however, active PFC complexes the simple SMPS circuit with additional PFC control loop such as predictive current mode control (Choi et al, 2018), modulated carrier control (Kim, et al, 2018), sliding mode (Mallik et al, 2018) and with advanced design such as delta/hexagon transformer design reported in a 3-Phase power line where a nine phase shifted uncontrolled diode bridges with interphase transformer is applied (Abdollahi, 2018).…”
Section: Introductionmentioning
confidence: 99%